1st European Symposium on Phytochemicals in Medicine and Food—Insight into the conference. Issue 1 (30th December 2022) - Popović‐Djordjević, Jelena B.
Abstract: The University of Belgrade was chosen to host an international conference "1st European Symposium on Phytochemicals in Medicine and Food", that was successfully held on 7–9. September 2022 in Belgrade, the capital city of Serbia. The main goals of the conference were to promote the scientific achievements of researchers in the field of natural products and their implementation in food and medicine, as well as to bring together well recognized scientists from all around the world and young researchers that are starting their careers in the research fields covered by the conference topics. In that respect 1‐EuSPMF fulfilled the expectations of the participants and the organizers. Abstract : The University of Belgrade hosted an international conference "1st European Symposium on Phytochemicals in Medicine and Food", that was successfully held on 7–9. September 2022 in Belgrade, the capital city of Serbia. The conference brought together well recognized scientists from all around the world and young researchers that are starting their careers in the research fields covered by the conference topics. 1‐EuSPMF fulfilled the expectations of the participants and the organizers.